Frailty Index as a Predictor of Readmission in Patients With Head and Neck Cancer. (14th September 2021) - Voora, Rohith S.; Qian, Alexander S.; Kotha, Nikhil V.; Qiao, Edmund M.; Meineke, Minhthy; Murphy, James D.; Orosco, Ryan K.
Abstract : Objective: To evaluate the predictive utility of the Hospital Frailty Risk Score (HFRS), a stratification tool based on the ICD‐10 ( International Classification of Disease, Tenth Revision ), and other risk factors for 30‐day readmissions and mortality in a nationally representative cohort. Study Design: Retrospective database review. Setting: Nationwide Readmissions Database (2017). Methods: Patients with head and neck cancer who underwent major surgical procedures were identified from the 2017 Nationwide Readmissions Database, representing 116 medical centers nationwide. Bivariate and multivariable logistic regression methods were used to identify factors associated with unplanned 30‐day readmission, 30‐day readmission mortality, and increased length of hospital stay. Results: A total of 14, 420 patients underwent major head and neck cancer surgery. Unplanned readmission occurred in 11% of patients. The most common reasons for unplanned readmission were procedural complications (26.5%), sepsis (7.3%), and respiratory failure (3.9%). Elevated frailty index (HFRS ≥5) was identified in 22% of patients. Frailty was associated with higher 30‐day readmission rates (18.0% vs 9.5%, P <. 01), which held on multivariate modeling (odds ratio [OR], 1.59 [95% CI, 1.37‐1.85]). Frail patients spent more days in the hospital (8.2 vs 6.8, P =. 02) and incurred more charges across hospital stays (275, 000 vs 188, 000, P <. 01). Patients >75 years old (OR, 1.26 [1.03‐1.55]) and patients with electrolyte abnormalities (OR, 1.25 [1.07‐1.46] were significantly more likely to be readmitted. Conclusion: In this head and neck cancer surgical population, HFRS significantly predicted unplanned readmission. HFRS is a potential risk stratification tool and should be compared with other methods and explored in other cancer populations. Beyond the challenge of identifying at‐risk patients, future work should explore potential interventions aimed at mitigating readmission.